The fiscalization of autonomy. State, indigenous peoples and accountability - Víctor Leonel Juan-Martínez (Íconos)
This paper shows part of the results of a research project conducted to identify the tensions and meeting points between state institutions of transparency, fiscalization and the allocation of resources and their instruments (platform for the open government, internet portals, rules of operation, among other) with institutions and community proceedings. The study was carried out in 12 indigenous communities of different peoples and regions in the state of Oaxaca, Mexico. The revision of the mechanisms of citizen participation and the efficiency of state and community mechanisms made it possible to observe until what point some favor or hinder accountability, as well as the need for an intercultural vision that can create dialogue between communities and state institutions. In that context experiences of “community comptroller” were revised with an emphasis placed on the successful mechanisms based on local norms with a high level of legitimacy, but also pointing out their limitations. Among its findings, this research shows that there is a high capacity for institutions of indigenous communities to guarantee accountability, as well as the lack of cultural relevance of the institutions of the Mexican State to recognize these mechanisms and establish coordination plans to contribute to this objective and the problems that are generated due to the gap between these two areas.